DEVELOPMENT OF PROBLEM BASED LEARNING MODEL TO IMPROVE STUDENTS' UNDERSTANDING (LITERATURE STUDY) - Yaqinah, Ainil (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Many students find the subject of Islamic religious education boring and try to avoid it. One of the reasons for this opinion is that the teacher's teaching method is still traditional and students feel bored and uncomfortable in the classroom. The purpose of learning Islamic religious education is to train students to become people of faith and belief, noble character, and equipped with knowledge and skills to practice Islamic teachings. One of the learning models that can be used to improve students' understanding of PAI learning is the problem-based learning (PBL) model. PBL is a student-centered learning model. In this model, students are faced with complex and difficult problems that they must solve. Students then work together in groups to solve the problem using the knowledge and skills they have. This research uses library research method, which is a method that collects information by understanding and examining theories in scientific literature.